Penyadartahuan Cinta Lingkungan Pesisir dan Laut Bagi Anak Pesisir Melalui Gerakan Peduli Sampah di Desa Puupi: Awareness of Love for Coastal and Marine Environment for Coastal Children Through the Waste Care Movement in Puupi Village - Nurhuda Annaastasia; roslindah Daeng Siang; risfandi risfandi; Seventry Meliana Patiung; akhmad mansyur; rosmawati rosmawati; Nurdiana A; La Ode Muh. Gunawan Giu (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Marine debris is waste that comes from human daily activities that are intentionally or unintentionally dumped around the coast / sea. So that the impact caused by marine debris can disrupt the food chain of marine life and even threaten their lives. In addition, people living around the coast will feel the negative impacts of marine debris, including health problems, bringing floods, eyesore, causing unpleasant odors and economic activities will be disrupted. The purpose is to provide an introduction to marine life and coastal ecosystems to coastal children in order to foster a love for coastal and marine conservation. This service activity is carried out in several stages: observation, poster media design design design as a delivery of information to the community and waste care actions. The results show that waste care action activities can foster the concern of coastal children as a maritime generation for the coastal and marine environment. In addition, the installation of posters related to the types of waste and the time of decomposition of the waste becomes a media message to always protect the environment.